Just hearing about it makes me feel so humiliated: Emotional and motivational responses to vicarious group-based humiliation - Vorster, A.; Dumont, K. B.; Waldzus, S. (International Review of Social Psychology, 2021)
Witnessing a fellow ingroup member being humiliated might be the most common situation in which intergroup humiliation is experienced. Humiliation on a group level is as complex as humiliation on an interpersonal level because of shared appraisals with other emotions. We propose that witnessing a fellow ingroup member being negatively stereotyped by an outgroup member elicits anger and/or shame insofar as it is appraised as vicariously humiliating leading to anger-related approach and shame-related avoidance. Evidence for this proposition was experimentally assessed in three studies using two intergroup contexts: nationality (Study 1: n = 291) and gender (Study 2: n = 429 females and Study 3: n = 353 males). Across these intergroup contexts, the group-devaluing event emphasizing a negative ingroup stereotype evoked anger-related approach and shame-related avoidance indirectly through vicarious humiliation. We conclude that the accompanying emotions and thus resulting motivations determine whether vicarious humiliation results in intergroup conflict.